Human rights protection in the context of combating terrorism: problems of finding the optimal balance - Voloschuk, Oksana; Kolesnyk, Viktoriia; Shevchuk, Andrii; Yushchyk, Olena; Krainii, Pavlo (Creative Commons CC-BY 4.0, 2021)
The article examines the essence and nature of terrorism in the light of the problem of observance and protection of human rights, as well as analyzes the problems that arise in the implementation of anti-terrorist activities. Emphasis is placed on the fact that it is difficult to find a balance in the observance of human rights in the implementation of various antiterrorist measures by law enforcement agencies and the investigation of crimes related to terrorist activities. It is concluded that the fight against terrorism and the protection of human rights are goals that cannot conflict with each other in a democratic society. They complement and mutually reinforce each other, so when taking measures to stop terrorist activities, states are obliged to adhere to key principles and norms of international law, as well as specific commitments made in connection with participation in international human rights agreements.
Захист прав людини в умовах боротьби з тероризмом: проблеми пошуку оптимального балансу
Keywords: terrorism; terrorist activity; human rights; restriction of human rights; counteraction to terrorism